Pengaruh Motivasi Intrinsik dan Kompensasi terhadap Kinerja Karyawan PT. Kereta Api Indonesia Logistik Kota Madiun - Aktaviani Putri, Deffiani; Iryanti, Endang (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this research is to determine the influence of intrinsic motivation and compensation on the employees performance at PT. Kereta Api Indonesia Logistics in Madiun City. The population of employees at PT. Kereta Api Indonesia Logistics in Madiun City is 35 employees, and the sampling method used is a saturated sampling technique, making all employees participants in the research. The research method employed is quantitative with a measurement scale using the ordinal scale with the Likert scale weighting technique ranging from 1 to 5. To achieve the research objectives, the hypotheses are tested using the Partial Least Square (PLS) software. The entire testing process using PLS demonstrates results that surpass the required values for the reliability of the testing. Based on the research findings, it is established that both intrinsic motivation and compensation have a significant positive effect on the employees performance at PT. Kereta Api Indonesia Logistics in Madiun City.